Nilai-Nilai Moderasi Beragama Dalam Tradisi Sedekah Bumi - Riscaga, Metta Riscaga; Eko Siswoyo (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya Wonogiri, 2024)
Tradition is a cultural heritage that has existed since ancient times. Tradition is a legacy of the Woyang ancestors that is preserved until now. Tradition is a culture, one form of tradition is the earth alms tradition. The earth alms tradition is a cultural heritage from ancestors that is still maintained until now. The earth alms tradition is a form of gratitude from society to nature for the abundant produce of the earth. In its implementation, a tradition has good norms in the community environment. Just like the earth alms tradition, in the earth alms tradition there are various values ​​of religious moderation in it which are good norms in society. This article is compiled using a descriptive qualitative method. The results of the discussion refer to the implementation of the earth alms tradition, in which there are values ​​of religious moderation. Where the values ​​of religious moderation in the earth alms tradition create harmony. Tradisi merupakan sebuah warisan budaya yang sudah ada sejak jaman dahulu kalah. Tradisi merupakan sebuah warisan nenek woyang yang dilestarikan hingga sekarang. Tradisi adalah sebuah budaya salah satu bentuk dari tradisi ialah tradisi sedekah bumi. Tradisi sedekah bumi merupakan warisan budaya dari leluhur yang masih terus dipertahankan hingga sekarang. Tradisi sedekah bumi merupakan bentuk syukur masyarakat terhadap alam atas hasil bumi yang melimpah. Dalam pelaksanaanya sebuah tradisi memiliki suatu norma-norma baik dalam lingkungkan masyarakat. Sama seperti tradisi sedekah bumi dimana dalam tradisi sedekah bumi terdapat berbagai nilai-nilai moderasi beragama didalamnya yang dimana merupakan norma-norma baik dalam bermasyrakat. Artikel ini disusun menggunakan metode kualitatis deskritif. Hasil pembahasan merujuk pada pelaksanaan tradisi sedekah bumi yang diamana di dalamnya terdapat nilai-nilai moderasi beragama. Dimana nilai-nilai moderasi beragama dalam tradisi sedekah bumi menciptakan sebuah kerukunan.